2005
DOI: 10.1111/j.1439-0450.2005.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Mastitis: A Review of Transmission and Control

Abstract: The Mycoplasma sp. that cause mastitis are simple, cell wall-less, bacteria that can colonize and cause diseases in other extramammary sites in the bovine. Prevalence of mycoplasma mastitis appears to be increasing in many locations throughout the world. The best method to identify this group of pathogens is through direct culture on mycoplasma agar media. However, limitations with this culture procedure are the duration of culture, 10 days, special conditions required and thus added expense, and the lack of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 52 publications
7
115
0
10
Order By: Relevance
“…The major causal microorganisms are bacteria, but mycoplasma, fungi and algae have also been reported to cause mastitis problems in some herds or regions [25][26][27][28]. It is very much interesting, about 137 species and subspecies of possible pathogens can be accompanying with infection of the mammary gland [29].…”
Section: Mastitis Pathogensmentioning
confidence: 99%
“…The major causal microorganisms are bacteria, but mycoplasma, fungi and algae have also been reported to cause mastitis problems in some herds or regions [25][26][27][28]. It is very much interesting, about 137 species and subspecies of possible pathogens can be accompanying with infection of the mammary gland [29].…”
Section: Mastitis Pathogensmentioning
confidence: 99%
“…Losses caused by clinical mastitis include: reduced milk yield and quality, costs of veterinary care, discarded milk and shortening of productive life [2,5]. Cows with subclinical mastitis do not show a visible udder inflammation and can be diagnosed by somatic cell count (SCC) and by detection of the presence of the pathogens.…”
Section: Occurence Of Mastitis In Dairy Cows Situated In Marginal Parmentioning
confidence: 99%
“…Approximately 10 mL of milk sample was taken into sterile tubes from udders aseptically and transferred to labortory in cold chain conditions. In addition, 19 M. bovis positive milk samples provided from a previous study [14] were included for use in mPCR tests. …”
Section: Milk Samplesmentioning
confidence: 99%
“…Losses due to M. bovis mastitis in the USA have been estimated as 108 million/year dollars and the proportion of disease in infected herds has been reported over the 70% [12] . Recent studies indicated that the prevalence of mycoplasmal mastitis has increased in most regions of the world in last years [13,14] .…”
Section: Introductionmentioning
confidence: 99%